Analysis of the Implementation of Technology-based Outdoor Learning Model in Science Subject (Plant Diversity) - Iseu Laelasari (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2021)
This study aimed to analyze the implementation of online learning strategies with technology-based outdoor learning models in science learning particularly in the unit of plant diversity in the environment for students MI NU Nurul Haq Prambatan, Kudus 4th class. Researchers used descriptive qualitative methods with research samples of class 4 teachers, 20 students and students’. Data collection was carried out through in-depth interviews and online questionnaires through Google form. The results show that the implementation of online learning strategies with technology-based outdoor learning was considered effective, flexible, easy to apply and provides benefits in enrich new insight or knowledge, reducing boredom and adding variety of methods in online learning in science learning. The implementation of technology-based outdoor learning in science learning by using plant identification applications can increase the knowledge of students, especially the scientific names of plants found in the yard, fields, gardens or on the side of the road in the home environment of each student. In addition, the activeness and participation of students in completing tasks appears to be higher when compared to online learning through regular assignments. Communication was well established between teachers, students, and parents during learning with the outdoor learning strategy.